Comparing nursing instructors and fourth-year nursing students' perspectives on clinical education problems - Mohammad Zahed Rokhzadi; Kambiz Zehni (Kurdistan University of Medical Sciences, 2015)
Background and Aim: Clinical education is the heart of nursing education. It is a complex process which is affected by different factors. Identifying the problems of clinical education is the first step to resolving them. The aim of this study was to compare nursing instructors and fourth-year nursing students' perspectives on problems with clinical education. Methods: This descriptive-analytical study was conducted in 2007-2008. The census method was employed for recruiting twenty one nursing instructors and 130 fourth-year nursing students from the Nursing and Midwifery Faculty of Kurdistan University of Medical Sciences, Sanandaj, Iran. A 39-item questionnaire was used for assessing the problems of clinical nursing education. Study data were analyzed by using the SPSS software. Findings: Most of the participating students (58.2%) noted that pre-clinical education suffers from many problems while most of the nursing instructors (66.7%) highlighted that the problems of pre-clinical nursing education are moderate. On the other hand, most of the students (53.4%) and instructors (73.7%) evaluated the problems of clinical education environment as moderate. Finally, most of the students (49.1%) and instructors (52.6%) highlighted that the problems of clinical evaluation are moderate. Conclusion: Pre-clinical education, clinical education environment, and clinical evaluation are problematic. Providing and improving educational facilities as well as revising clinical evaluation procedures are recommended.